Enrichment of organic material with Trichoderma asperellum for the management of twisted disease on shallot - Ilma, Hurin Nabila Aghnia; Wibowo, Arif; Joko, Tri; Subandiyah, Siti; Harper, Stephen (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Shallots are a type of plant used as a flavoring agent and are often affected by twisted disease caused by Fusarium spp. This study aims to determine the ability of organic material enriched by Trichoderma asperellum in controlling twisted disease, increasing production, and suppressing the population of Fusarium spp. in the soil. The research showed that compost and chicken manure enriched with T. asperellum in a ratio (200:1) were able to reduce the disease incidence compared to controls, in addition to increasing production and suppressing the population of Fusarium spp. in the soil. The colonies of Fusarium spp. in the soil were correlated with disease incidence in each treatment. The highest incidence of twisted disease was followed by the number of Fusarium spp. colonies. The microbial composition did not affect disease suppression when observed using a dependent method using PCR-RISA. The microbial composition with the dependent method using PCR RISA did not affect the suppression of the twisted disease in the shallot plants.